Purificação e caracterização de uma fosfolipase A2 do veneno amarelo de serpentes Crotalus durissus collilinetaus - SANTANA, Pedro Henrique Camargo (2009)
In Brazil, the snake Crotalus durissus collilineatus is much studied, particularly its component crotoxina. The crotoxina is the most toxic component of venom from the species cascavéis amicanas Crotalus durissus. It is composed of two different subunits, the crotapotina (acid component) and a phospholipase A2 (basic component). The enzyme phospholipase A2 is the most studied of these poisons, being largely responsible for its toxicity. Its main effects are neurotoxicity, myotoxicity, cytotoxicity, platelet aggregation, anti-coagulant and bactericide. This study aims to purify and characterize a new phospholipase A2 isolated from Crotalus durissus collilineatus, and uses it as a model for studies of compounds with potential antinflamatório. Samples (5mg) of crude venom of Crotalus durissus collilineatus were applied on a C18 column coupled to a system semipreparativa HPLC. 20 peaks were obtained for proteins / peptides, and the increased activity of fofolipase (PLA) was detected in fraction 14. This fraction was subjected to a new phase chromatography on C18 analytical column, resulting in the isolation of a new PLA. By electrophoresis, SDS-PAGE the enzyme showed high degree of purity, with molecular mass around 13 kDa. The PLA2 activity showed optimal at pH of 8.2 and at temperatures between 35-40 º C and remains stable up to temperatures of 60 º C. According to our experiments isolated PLA was inhibited Ca2 +, and activity was not changed by Cu2 +. Manaca extract, ellagic acid and quercetin strongly inhibited the PLA, showing that this enzyme has potential for the selection of compounds with potential antiinflammatory.